Terorisme atas Nama Agama - Abdul Muis Naharong (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2013)
In the wake of 9/11 the role of religion in promoting acts of violence considered as terrorism has been widely discussed by scholars, journalists, and policy makers. Several scholars, however, claim that religion does not have anything to do with terrorism. In their views religion is innocent and victim of unscrupulous political activists. Several others do believe that religion has to do with terrorism because religion has the power to motivate people to do good as well bad things. This article aims to elaborate religious or sacred terrorism or ‘new terrorism’ according to some scholars. The first part of this article tries to elaborate the meanings of ‘terrorism’ and ‘religion’, and to explain its root and trigger causes. The second part tries to discuss the opinions of scholars who claim that religious terrorism is real and not as a mere mask of other worldly interests, to elaborate the characteristics of religious terrorism, and to explain why religious terrorism is mostly associated with Islam.DOI: 10.15408/ref.v13i5.915